HUBUNGAN ANTAR KOMPONEN MIKROFASIES LERENG TERUMBU DAN CEKUNGAN LOKAL BELAKANG TERUMBU PADA BATUGAMPING BIOKLASTIKA FORMASI BATURAJA DI DAERAH SEKITAR MUARADUA, SUMATERA SELATAN - -, Sigit Maryanto (Bulletin of Scientific Contribution, 2010)
Bioclastic limestones from Baturaja Formation cropped out at Muaradua area, South Sumatera is a good object of research for studying microfacies of limestone. Based on the rock features under the polarization microscope of the bioclastic limestones taking from studied area could be predicted the limestones are predominantly deposited at reef-flank and back-reef local basin. The main components T-F-P test of the limestones showing a significant difference of the carbonate grains, terrigenous grains, and neomorphism materials between two depositional environments. The other side, matrix, cement, and rock porosity components have no significant difference.